1993
DOI: 10.1128/jb.175.14.4507-4514.1993
|View full text |Cite
|
Sign up to set email alerts
|

Importance of formylability and anticodon stem sequence to give a tRNA(Met) an initiator identity in Escherichia coli

Abstract: In bacteria, the free amino group of the methionylated initiator tRNA is specifically modified by the addition of a formyl group. The functional relevance of such a formylation for the initiation of translation is not yet precisely understood. Advantage was taken here of the availability of thefint gene, encoding the Escherichia coli Met-tRNA;Met formyltransferase, to measure the influence of variations in the level of formyltransferase activity on the involvement of various mutant tRNAftet and tRNA:jet specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
27
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 37 publications
(34 reference statements)
2
27
0
Order By: Relevance
“…These studies confirm the results of in vitro analyses and show that all the mutants that have a 1:72 base pair are active in elongation in vivo in E. coli and in Saccharomyces cerevisiae (10,19,29,35).…”
Section: Downloaded Fromsupporting
confidence: 77%
See 1 more Smart Citation
“…These studies confirm the results of in vitro analyses and show that all the mutants that have a 1:72 base pair are active in elongation in vivo in E. coli and in Saccharomyces cerevisiae (10,19,29,35).…”
Section: Downloaded Fromsupporting
confidence: 77%
“…This explains how a relatively limited number of nucleotides in the tRNA can specify all of the properties needed for initiation of protein synthesis. Further confirmation of this comes from the finding that introduction of the minimal sequences necessary for formylation and for P site binding onto elongator methionine and glutamine tRNAs allows these mutant tRNAs to act as initiator tRNAs in E. coli (10,34).…”
Section: Downloaded Frommentioning
confidence: 68%
“…1 (1)(2)(3)(4)(5)(6). In vitro studies of protein synthesis using extracts from Escherichia coli showed that translation was stimulated by fMettRNA fMet (7).…”
mentioning
confidence: 99%
“…The product of the fint gene plays an essential role for optimal growth of E. coli cells (13), possibly by enabling MetMet tRNAf to participate in the initiation rather than in the elongation step of the translation process (12). fnt is the second cistron of an operon whose first cistron, which we called fins, encodes a putative 19-kDa polypeptide (12,21). The translated amino acid sequence of fins shows a motif characteristic of neutral zinc aminopeptidases (16,17,25,29) (Fig.…”
mentioning
confidence: 99%
“…However, peptide deformylase could not be further characterized because of its extreme instability (1,18,28 (13). The product of the fint gene plays an essential role for optimal growth of E. coli cells (13), possibly by enabling MetMet tRNAf to participate in the initiation rather than in the elongation step of the translation process (12). fnt is the second cistron of an operon whose first cistron, which we called fins, encodes a putative 19-kDa polypeptide (12,21).…”
mentioning
confidence: 99%